Variation In Human Intelligence With Mood Disorders: Unraveling the Genetic Basis of Mood Disorders and its Impact on Human Intelligence (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Mood disorders arecomplex psychiatric disorders that are the leading cause of disability. Theyinclude major depressive disorder (MDD) and bipolar disorder (BD). Both arehighly heritable, i.e. the variance between individuals is, in MDD partly andin BD mostly, explained by genetic factors. Their specific genetic background,however, remains widely unknown. Previous linkage and association studies haverevealed some potential candidate genes and genomic areas that seem topredispose to mood disorders, at least in some populations and subsamples.Recent genome wide association (GWA) studies have revealed some novelsusceptibility genes and risk variants as the field has moved into the era ofgenome-wide genotyping of huge samples sizes from collaborative studies. Therisk variants revealed with this approach, however, cover only a small fractionof the total heritability of these diseases. They will definitely revealimportant etiological factors for the disease and might help to develop new,more efficient drugs, but they will not tell the whole story of genetics behindmood disorders.